Economic Empowerment of Dalits through I/NGOs - Biswakarma, Tilak (Humanities and Social Sciences Journal, 2023)
Empowerment is generally understood as raising people's present status by providing various means such as knowledge, skills, and resources. Currently, in Nepal, various I/NGOs are working in the field of political, social, and economic empowerment of poor and disadvantaged people through different programs and plans. International donors and the government working towards poverty alleviation have tended to give priority to Dalits because they are one of the poorest and most backward groups in Nepal. On one hand, Dalits' issues of development are being talked about by all sectors of Nepal, but their poverty rate is double the national average. Therefore, this study examined whether Dalit-focused development interventions lead to economic development. The findings of this study revealed the fact that everyone has experienced a change compared to the past, but it is very hard to determine the sole change maker. Also, the projects and programs have often had no meaningful participation from Dalits. Despite the widespread use of the term Dalit in the field of development, not a single project targeting Dalits is in operation. This fact indicates that the economic empowerment of Dalits is in only slogans and in the progress reports of the organizations rather than in a real sense. On the one hand, there is politics in the name of Dalit inclusion, and on the other hand, they are unable to prosper in their life from the support. The majority of Dalits' situations are almost the same in as the past whereas the majority of non-Dalits bring comprehensive change in their life. If this situation continues to lead to a huge socio-economic gap between Dalits and non-Dalits will be perilous for the future.